Penerapan Metode Demonstrasi dalam Pembelajaran Menulis Teks Prosedur pada Siswa Kelas XI SMAN 1 Juntiyuat Tahun Pelajaran 2022/2023 - Tia Wati; Muhammad Sholeh; Tobroni Tobroni (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This study aims to improve learning in class XI SMA N 1 Juntiyuat by using the demonstration method so students don't get bored quickly, and students' attention is focused on learning so as to make learning more enjoyable. Thlis study used an experimental study withl 23 students in class XI IPS 1 as thle experimental class and 22 students in class XI IPS 2 as thle colntroll class. Thle methlold olf colllecting data in thlis study was bly colllecting data frolm olblservatiolns and tests (pretest and polsttest). BLased oln statistical results using twol independent t tests (independent samples t test), a tcolunt olf 5.560 is olbltained and a ttablle olf 1.714. Sol tcolunt (5.560) > ttablle (1.714). Thlus, it can ble stated thlat thle applicatioln olf thle demolnstratioln methlold is effective in learning tol write prolcedural texts in class XI students olf SMAN 1 Juntiyuat in thle 2022/2023 academic year. BLased oln thle results olf olblservatiolns made, it is evident thlat thle applicatioln olf thle demolnstratioln methlold can increase thle activeness olf students in learning tol write prolcedural texts in class XI SMA N 1 Juntiyuat.